2018
DOI: 10.1007/s12182-018-0279-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk measurement of international oil and gas projects based on the Value at Risk method

Abstract: International oil and gas projects feature high capital-intensity, high risks and contract diversity. Therefore, in order to help decision makers make more reasonable decisions under uncertainty, it is necessary to measure the risks of international oil and gas projects. For this purpose, this paper constructs a probabilistic model that is based on the traditional economic evaluation model, and introduces value at risk (VaR) which is a valuable risk measure tool in finance, and applies VaR to measure the risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, he also used the simulation results to compare the impact of different risk factors on the project's net present value. e results show that (1) Risk has a great influence on the project's net present value; therefore, if the risk is ignored, the decision may be wrong; (2) e simulation method is used to simulate the random distribution of risk factors in the probability model, so the probability is related to the project's net present value [5]. Trofimov V T found that onshore oil and gas production is often accompanied by accidents of varying severity and negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, he also used the simulation results to compare the impact of different risk factors on the project's net present value. e results show that (1) Risk has a great influence on the project's net present value; therefore, if the risk is ignored, the decision may be wrong; (2) e simulation method is used to simulate the random distribution of risk factors in the probability model, so the probability is related to the project's net present value [5]. Trofimov V T found that onshore oil and gas production is often accompanied by accidents of varying severity and negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Wind speed fluctuations and time-varying system parameters will affect the stability of the power grid. The instability of wind power output has become a bottleneck restricting the development of wind power [7]. For the problem of control system uncertainty and disturbance, an output feedback control method is proposed and the effectiveness of the method is verified in [8]- [9].…”
Section: Introductionmentioning
confidence: 99%